Multiparametric MRI guidance in first-time prostate biopsies: what is the real benefit? - Acar, Omer; Esen, Tarik; Colakoglu, Bulent; Vural, Metin; Onay, Aslihan; Saglican, Yesim; Tuerkbey, Baris; Rozanes, Izzet (TURKISH SOC RADIOLOGY, 2015)
PURPOSE With the increased recognition of the capabilities of prostate multiparametric (mp) magnetic resonance imaging (MRI), attempts are being made to incorporate MRI into routine prostate biopsies. In this study, we aimed to analyze the diagnostic yield via cognitive fusion, transrectal ultrasound (TRUS)-guided, and in-bore MRI-guided biopsies in biopsy-naive patients with positive findings for prostate cancer screening. METHODS Charts of 140 patients, who underwent transrectal prostate biopsy after the adaptation of mp-MRI into our routine clinical practice, were reviewed retrospectively. Patients with previous negative biopsies (n=24) and digital rectal examination findings suspicious for >= cT3 prostate cancer (n=16) were excluded. T2-weighted imaging, diffusion-weighted imaging, and dynamic contrast-enhanced imaging were included in mp-MRI. Cognitive fusion biopsies were performed after a review of mp-MRI data, whereas TRUS-guided biopsies were performed blinded to MRI information. In-bore biopsies were conducted by means of real-time targeting under MRI guidance. RESULTS Between January 2012 and February 2014, a total of 100 patients fulfilling the inclusion criteria underwent TRUS-guided (n=37), cognitive fusion (n=49), and in-bore (n=14) biopsies. Mean age, serum prostate specific antigen level, and prostate size did not differ significantly among the study groups. In TRUS-guided biopsy group, 51.3\% were diagnosed with prostate cancer, while the same ratio was 55.1\% and 71.4\% in cognitive fusion and in-bore biopsy groups, respectively (P = 0.429). Clinically significant prostate cancer detection rate was 69.1\%, 70.3\%, and 90\% in TRUS-guided, cognitive fusion, and in-bore biopsy groups, respectively (P = 0.31). According to histopathologic variables in the prostatectomy specimen, significant prostate cancer was detected in 85.7\%, 93.3\%, and 100\% of patients in TRUS-guided, cognitive fusion, and in-bore biopsy groups, respectively. CONCLUSION In the first set of transrectal prostate biopsies, mp-MRI guidance did not increase the diagnostic yield significantly.